Identification of Sex of the Skeleton Recovered from the Cemetery at Sowinki Near Poznań on the Basis of Genetic Analysis of Hair Remains - Krzyszowski, Andrzej; Stochaj, Marian; Pawłowski, Ryszard; Welz, Anna (Anthropological Review, 1996)
The authors present the results of archeological, forensic, and genetic analysis of human hair remains recovered from one of the graves of an eary mediaeval cemetery at Sowinki, near Poznań. Genetic analysis based on the amplification of DNA (PCR method) and electrophoresis has confirmed an earlier archeological presumption that the skeleton in question belonged to a woman.